Determinants of Inflation in a Transition Economy : The Case of Ukraine - Lissovolik, Bogdan (IMF Working Papers; Working Paper ;, 2003)
This paper examines determinants of inflation in Ukraine during 1993-2002 in a cointegrating framework. Two basic theoretical models-a markup and a money market model-are tested. While broad money is cointegrated with the CPI for the whole sample and for early subsamples, the cointegration ceases to be statistically significant between 1996-2002, in part because of strong remonetization. The mark-up model offers a more consistent and well-fitting overall framework for 1996-2002 data, pointing inter alia to a greater role of administered prices in the CPI within a fairly mainstream inflation process. The "long-term" monetary transmission mechanism operates through the exchange rate and wages, but broad money clearly enters short-term inflation determinants. Prudent macroeconomic policies, grain harvests, and administrative decisions explain the sharp decline of inflation over 2000-2002.